Is the place of nitrates preserved in the treatment of heart failure? - I.V. Shklianka; O.A. Yepanchintseva; O.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
The clinical case demonstrates the advisability of using long-acting nitrates in a revascularized patient with multivascular lesions of the coronary arteries and increased signs of heart failure. According to current international guidelines, the use of nitrates should be considered in addition to basic therapy of heart failure in case of decompensation of blood circulation, as well as in combination with hydralazine in case of intolerance to renin-angiotensin system blockers, and not only in case of heart failure of ischemic etiology.